Overgroups of root groups in classical groups - Aschbacher, Michael, 1944- (Memoirs of the American Mathematical Society, 2016)
The author extends results of McLaughlin and Kantor on overgroups of long root subgroups and long root elements in finite classical groups. In particular he determines the maximal subgroups of this form. He also determines the maximal overgroups of short root subgroups in finite classical groups and the maximal overgroups in finite orthogonal groups of c-root subgroups.